1980
DOI: 10.1002/cd.23219800703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical child psychology: The need for developmental principles

Abstract: Clinical child psychology is in dire need of advances in diagnoses and treatment. The author suggests several ways this goal can be achieved through the application of developmental psychology. Clinical Child Psychology: The Need for Developmental Principles Sebastiano SantostefanoThe clinical child psychologist is in dire need of advances in diagnostic and treatment techniques and in concepts that guide what-is observed and how to understand these observations. Compared to earlier clinicians who worked primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Our review has revealed that there is an appreciable lack of interface between developmental psychology and clinical treatment with adolescents. This lack of attention has occurred despite numerous "calls" for research in this area (e.g., Holmbeck & Kendall, 1991;Santostefano, 1980;Tolan & Cohler, 1993). In this article, we have reviewed a Framework for Understanding Adolescence which illustrates the major developmental tasks of the adolescent period.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Our review has revealed that there is an appreciable lack of interface between developmental psychology and clinical treatment with adolescents. This lack of attention has occurred despite numerous "calls" for research in this area (e.g., Holmbeck & Kendall, 1991;Santostefano, 1980;Tolan & Cohler, 1993). In this article, we have reviewed a Framework for Understanding Adolescence which illustrates the major developmental tasks of the adolescent period.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Moreover, the work to date has not explored important developmental–adaptational considerations that may serve to clarify crucial aspects of the relationship between cognition and affect in maltreated children. The theory of cognitive control development proposed by Santostefano (1978) permits simultaneous emphasis on stages of development, mobility of functions, and the regulation of affects and appears to be extremely useful in guiding the study of cognition as it relates to emotion regulation.…”
mentioning
confidence: 99%
“…Cognitive controls are conceptualized as mechanisms that determine the ways in which the individual uniquely organizes, interprets, and makes use of information. These cognitive control processes can be measured reliably, follow explicit courses in development from immaturity to maturity, predict the emergence of learning disabilities, underlie intellectual and academic functioning, and define an individual's cognitive accommodations to changing environments (see Santostefano, 1978; 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study (Santostefano, 1980), also using an earlier form of this scale, compared youth hospitalized because of aggressive behaviors to nonaggressive youth hospitalized in the same facility. Among the findings observed, the aggressive youth produced fewer images depicting motion and interaction, suggesting that experiences with others tended to remain unsymbolized and embodied and had not yet been translated and available to the more conscious fantasy mode.…”
Section: Illustration Of New Directions In Research and Treatment Tecmentioning
confidence: 99%